Tariq bin zeyad - Safdar, Shaheen (Children Publication Karachi, 2004)
Tariq ibn Ziyad was a legendary Umayyad general who led the Muslim conquest of the Iberian Peninsula in 711 AD. His audacious crossing of the Strait of Gibraltar with a relatively small army and his decisive victory at the Battle of Guadalete marked a turning point in European history. The name "Gibraltar" itself is derived from "Jabal Tariq," meaning "Mountain of Tariq," a testament to his enduring legacy.